Efficacy of Perilla frutescens (L.) Britton var. frutescens extract on mild knee joint pain: A randomized controlled trial - Kim, NamHoon; Kim, Si-Yeon; Kim, Sang-Woo; Lee, Jung Min; Kim, Sung-Kyu; Park, Mi-Houn; Kim, Ki-Hwan; Oh, Minseok; Son, Chang-Gue; Jung, In Chul; Lee, Eun-Jung (Frontiers in Pharmacology, 2023)
Objectives: This study aimed to evaluate the efficacy and safety of PF extract (PFE) in sub-healthy people with mild knee pain. Methods: A randomized, double-blind, two-arm, single-center, placebo-controlled clinical trial was conducted. Individuals with knee joint pain and a visual analogue scale (VAS) score <50 mm were included in the study, and participants with radiological arthritis were excluded. Participants were administered either PFE or a placebo capsule (700 mg, twice a day) orally for eight weeks. The comparisons of the changed VAS score and Western Ontario and McMaster Universities Osteoarthritis (WOMAC) scores between the PFE and placebo groups were primary outcomes, while the five inflammation-related laboratory tests including cartilage oligomeric matrix protein, cyclooxygenase-2, neutrophil and lymphocyte ratio, high sensitive C-reactive protein, and erythrocyte sedimentation rate were secondary outcomes. Also, a safety assessment was done. Results: Eighty participants (mean age, 38.4 ± 14.0, male: female, 28:52) were enrolled; 75 completed the trial (PFE 36 and placebo 39). After eight weeks, both VAS and WOMAC scores were reduced in the PFE and placebo groups. The changed scores were significantly higher in the PFE group compared to the placebo group: 19.6 ± 10.9 vs. 6.8 ± 10.5; VAS scores (p < 0.001), and 20.5 ± 14.7 vs. 9.3 ± 16.5; total WOMAC scores (p < 0.01) including the sub-scores for pain, stiffness, and functions. No significant changes were reported in the five inflammation-related laboratory parameters. All adverse events were considered minor and unlikely to result from the intervention. Conclusion: The PFE is safe and effective for pain reduction and function improvement in sub-healthy individuals with mild knee pain. Trial registration name: Efficacy of Perilla frutescens (L.) Britton var. frutescens extract on mild knee joint pain: a randomized controlled trial; Registration number: CRIS: KCT0007219 https://cris.nih.go.kr/cris/search/detailSearch.do?search_lang=E&focus=reset_12&search_page=M&pageSize=10&page=undefined&seq=23101&status=5&seq_group=19745.